On Typology of Polish and French Imperfective - Karolak, Magdalena (Lingua Posnaniensis, 2011)
The aim of this paper is to present a typology of Polish imperfective past tense forms in the factual use for the purpose of creating a set of guidelines for their translation into French language. Although descriptions of factual imperfective aspect is not new to linguistics, both Polish and international, equivalence of its forms in other languages pose problems to foreigners and native speakers alike. This is especially true in French, where Polish past imperfective forms could be expressed by a number of past tenses. In order to proceed with our task we are going to adopt a classification of Polish imperfective verbal forms based on the following criteria: general factual meaning or specific (concrete) factual meaning as a primary measure and imperfective or perfective intention of the imperfective form as a secondary measure. Such systematization of the phenomenon in Polish will allow us to formulate guidelines of equivalence with French past tenses.